The Concept And Position Of The Formulation Of The Law Of The Republic Of Indonesia Number 11 Of 2020 Concerning Job Creation Was Prepared Using The Omnibus Law Technique - DUNGGA, Weny A; MUHTAR, Mohamad Hidayat (Protection: Journal Of Land And Environmental Law, 2022)
The application for judicial and formal review of the Job Creation Law was registered on November 12, 2020, with Case Number: 103/PUU-XVIII/2020. Regarding the formal test, KSBSI took issue with forming the Government Job Creation Law. This research uses a legal approach, which is to review all relevant. Data collection in normative legal research is divided into 3 (three) types or 3 (three) secondary data collection methods: literature studies, documents and archival studies. The Omnibus Bill or Omnibus Law is a technique for drafting laws and regulations that were drafted with the aim of the President overcoming regulatory obesity. Even though the technique for drafting the Omnibus Law, in terms of suitability of the writing format with Attachment II to the Law of the Republic of Indonesia Number 12 of 2011 concerning the Formation of Legislation, there are contradictions. The ratification of the Omnibus Law as a law means that the Omnibus Law, in the perspective of the Legislation hierarchy, is considered the same as other laws which are not prepared using the omnibus law method. However, you need to know after the Constitutional Court's decision, the Law of the Republic of Indonesia Number 11 of 2020 concerning Job Creation is declared valid and must be corrected within two years at the latest. Otherwise, it will be declared permanently unconstitutional